Allelopathy of Ethanol, Ethyl Acetate, and Aquadest Extracts of Kirinyuh (Chromolaena odorata) Leaves as a Bioherbicide in Controlling Spenochlea zeylanica - Rahmadi, Rizky; Rochman, Fajar; Subarjo, Subarjo (ABEC Indonesia, 2024)
Spenochela zeylanica is the most prevalent weed of paddy rice in Indonesia, and therefore its presencenecessitates control in order to reduce the potential for yield losses. The use of chemical herbicides as a control method isprevalent, but their environmental impact and potential for inducing weed resistance are significant drawbacks. It istherefore necessary to identify control methods that are environmentally friendly and capable of overcoming weedresistance. The leaves of Chromolaena odorata have allelopathic properties that could be harnessed for use as abioherbicide. The objective of this study is to evaluate the efficacy of C. odorata leaf extractions using diverse organicsolvents as a bioherbicide for the management of S. zeylanica. This study used a randomized group design (RBD) with 11treatments and 3 replications, including: T0: no treatment; 96% ethanol extraction: T1(5%), T2(10%), T3(15%); ethylacetate extraction: T4(5%), T5(10%), T6(15%); aquadest extraction: T7(5%), T8(10%), T9(15%); T10: 2,4-D herbicide(648 g a.i./ha). The findings indicated that the extraction of C. odorata using various organic solvents exhibited promise asa bioherbicide, displaying the capacity to poison weeds up to 100% (T2, T3, T6, T8, T9) and effectively suppressing theheight, root development, and chlorophyll content of S. zeylanica.